Implementation of technology for the formation of information and communication competence among future choreographers - Olena Avramenko; Serhii Humeniuk (Kazimierz Wielki University, 2020)
The article is devoted to one of the current problems in vocational education - the formation of future choreographers information and communication competence (ICC). The author defines the essence of the concept of "information and communication competence". The article emphasizes that the result of the formation of choreographers information and communication competence in the learning process is the formed competence for this type of activity. When substantiating and developing the technology, the following stages of its implementation are distinguished: motivational, cognitive and technological. All three stages of the developed technology are aimed at the formation of future choreographers of information and communication competence. In the process of professional training of future choreographers for professional activity by means of information and communication technologies the criteria (motivational, semantic, reflective) and levels of formation (high, average, low) are specified. 128 respondents of the first and second courses of the Faculty of Arts of theG.S.SkovorodaKharkivNationalPedagogicalUniversitytook part in the pedagogical research (by consent). The control group consisted of 66 people (CG), and the experimental group - 62 people (EG). The article describes the stages of technology implementation. At the control stage of the pedagogical experiment with the help of methods of mathematical statistics the results of the research were obtained, on the basis of which the efficiency of the introduced technology of information and communication competence formation was proved.